1997
DOI: 10.1128/jcm.35.2.468-470.1997
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Helicobacter pylori infection in a cohort of children monitored from 6 months to 11 years of age

Abstract: A cohort of Swedish children was monitored from 6 months to 11 years of age. Immunoglobulin G (IgG) and IgA antibodies to Helicobacter pylori were measured in 1,857 serum samples, drawn at the ages of 6, 8, 10, 18 months and 2, 4, and 11 years. Of the 294 children, 40 (13.6%) were found to have been infected at some time. However, at 11 years of age, only 6 of 201 (3%) children were seropositive. The highest seroprevalence of positive results, 10%, was found at 2 years of age, and the highest incidence of 13.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
72
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(83 citation statements)
references
References 11 publications
9
72
0
2
Order By: Relevance
“…23,24,26 Although we found a borderline significant association in our study, the magnitude and direction of observed effect estimate were in the expected pattern, and our analyses were limited by insufficient statistical power as a result of the low prevalence of H. pylori infection at age 6.5 years. The low prevalence of H. pylori infection at the age of 6.5 follow-up visit in this cohort may be linked to spontaneous elimination of the bacterium, 69 or better attention to health issues in older children, or use of antibiotics for other common diseases. 70 Further study is warranted to understand the exact reason of declining H. pylori prevalence in older children in Ethiopia.…”
Section: Potential Confounders Of Atopymentioning
confidence: 93%
“…23,24,26 Although we found a borderline significant association in our study, the magnitude and direction of observed effect estimate were in the expected pattern, and our analyses were limited by insufficient statistical power as a result of the low prevalence of H. pylori infection at age 6.5 years. The low prevalence of H. pylori infection at the age of 6.5 follow-up visit in this cohort may be linked to spontaneous elimination of the bacterium, 69 or better attention to health issues in older children, or use of antibiotics for other common diseases. 70 Further study is warranted to understand the exact reason of declining H. pylori prevalence in older children in Ethiopia.…”
Section: Potential Confounders Of Atopymentioning
confidence: 93%
“…The prevalence rates of gastritis and hence H. pylori infection were similar in Finland and in Estonia among persons born before World War II, whereas higher prevalence rates were consistently noted among persons born after 1945 in Estonia compared with Finland [8]. According to the studies conducted in the 1990s, the uniformly very high seroprevalence rate of H. pylori infection, 89-94%, was found for all decades of life among persons aged 30-79 years in Estonia [9], whereas in Finland the prevalence rate decreased with age, from 68% in the age group 65-74 years to 9% in the age group 25-34 years [7]; as many as 56% of children aged 9-15 were seropositive in Estonia [10] vs. 3% among 11-year-old children in Sweden [11] and 5.7% among 12-year-old children in Finland [12]. Although Estonia, Finland and Sweden are geographically close, it is apparent that the patterns of prevalence of H. pylori infection in them are different.…”
mentioning
confidence: 88%
“…In previous studies, our group has shown a high prevalence of H. pylori infection, using 13 C-urea breath test (UBT) to diagnose the infection, in children living in a low-income urban community of the northeast of Brazil with homogeneous socioeconomic status [16].…”
mentioning
confidence: 99%